Orexin 1 Receptor Antagonism in the Basolateral Amygdala Shifts the Balance From Pro- to Antistress Signaling and Behavior - Yaeger, Jazmine D.W.; Krupp, Kevin T.; Jacobs, Benjamin M.; Onserio, Benard O.; Meyerink, Brandon L.; Cain, Jacob T.; Ronan, Patrick J.; Renner, Kenneth J.; DiLeone, Ralph J.; Summers, Cliff H. (Biological psychiatry (1969), 2022)
Stress produces differential behavioral responses through select molecular modifications to specific neurocircuitry elements. The orexin (Orx) system targets key components of this neurocircuitry in the basolateral amygdala (BLA). We assessed the contribution of intra-BLA Orx1 receptors (Orx1Rs) in the expression of stress-induced phenotypes of mice. Using the Stress Alternatives Model, a social stress paradigm that produces two behavioral phenotypes, we characterized the role of intra-BLA Orx1R using acute pharmacological inhibition (SB-674042) and genetic knockdown (AAV-U6-Orx1R-shRNA) strategies. In the BLA, we observed that Orx1R (Hcrtr1) messenger RNA is predominantly expressed in CamKIIα+ glutamatergic neurons and rarely in GABAergic (gamma-aminobutyric acidergic) cells. While there is a slight overlap in Hcrtr1 and Orx2 receptor (Hcrtr2) messenger RNA expression in the BLA, we find that these receptors are most often expressed in separate cells. Antagonism of intra-BLA Orx1R after phenotype formation shifted behavioral expression from stress-sensitive (Stay) to stress-resilient (Escape) responses, an effect that was mimicked by genetic knockdown. Acute inhibition of Orx1R in the BLA also reduced contextual and cued fear freezing responses in Stay animals. This phenotype-specific behavioral change was accompanied by biased molecular transcription favoring Hcrtr2 over Hcrtr1 and Mapk3 over Plcb1 cell signaling cascades and enhanced Bdnf messenger RNA. Functional reorganization of intra-BLA gene expression is produced by antagonism of Orx1R, which promotes elevated Hcrtr2, greater Mapk3, and increased Bdnf expression. Together, these results provide evidence for a receptor-driven mechanism that balances pro- and antistress responses within the BLA.